Pengembangan Budaya Literasi Membaca Al- Qur'an Di SMK PAB 1 Helvetia dan SMK PAB 2 Helvetia - Mawardani, Sulis; Dahlan, Zaini; Dani, Sulis Mawar (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
Currently, the instruction of Al-Qur'an Hadith in classes X at SMK PAB 1 Helvetia and SMK PAB 2 Helvetia lacks the utilization of diverse instructional media, resulting in decreased student motivation towards learning. The objective of this project is to create educational media for Android devices and assess the viability of this media for learning purposes. This study employs the ADDIE development paradigm, which consists of five stages: analysis, design, development, implementation, and evaluation. The study was carried out at SMK PAB 1 Helvetia and SMK PAB 2 Helvetia, involving a total of 20 participants, from August to October 2022. The objective of the study was to assess the viability of the Android-based educational media that had been produced. The data gathering process encompassed many methods, including observation, questionnaires, validation, and testing. The data was subsequently subjected to analysis by converting the mean score into a percentage. The objective of the trial was to ascertain the students' reactions towards educational media. The findings indicated that the utilization of Android-based learning media for high school students in the context of fundamental geographic information system content was deemed highly valid. The media validation yielded a score of 80.5%, while the material validation yielded a score of 80.34%. The findings from the student response trials indicate a high level of interest among students in the learning medium employed, as evidenced by a practicality value of 82.5% in the small group and 83.5% in the big group